TRANSLATION SHIFT IN THE LITTLE MATCH GIRL SHORT STORY - Nur Mutmainna Halim (STKIP PGRI Jombang, 2021)
The paper discusses shifts occurred in the Indonesian translation of Little Match Girl. This research aims to investigate those translation shifts. Furthermore, researchers aimed to describe and calculate the frequency of shifts. This research methodology was descriptive qualitative. Data collection was done by collecting words, clauses and sentences that experienced a shift in translation. The data in this research are short story text ‘Little Match Girl’ in English by Hans Christian Andersen in 1845 and ‘Gadis Penjual korek Api’ in Indonesian by Harum L Wibowo in 2015. The results showed that: (1) all types of shifts occurred; level shifts, structure shifts, class shifts, unit shifts, and intra-system shifts (2) unit shifts counted as the most common shifts occured in the Indonesian translated version of Little Match Girl with 42 cases out of 121 units found. The present study may provide information in translation matters and could be considered as a contribution of a research-based samples to similar research in translation deals.Keywords: translations shifts,Little Match Girl, short story.